Gene expression analysis in prostate cancer: The importance of the endogenous control. Issue 4 (27th August 2012) - Vajda, Alice; Marignol, Laure; Barrett, Ciara; Madden, Stephen F.; Lynch, Thomas H.; Hollywood, Donal; Perry, Antoinette S.
Abstract BACKGROUND Aberrant gene expression is a hallmark of cancer. Quantitative reverse‐transcription PCR (qRT‐PCR) is the gold‐standard for quantifying gene expression, and commonly employs a house‐keeping gene (HKG) as an endogenous control to normalize results; the choice of which is critical for accurate data interpretation. Many factors, including sample type, pathological state, and oxygen levels influence gene expression including putative HKGs. The aim of this study was to determine the suitability of commonly used HKGs for qRT‐PCR in prostate cancer. METHODS Prostate cancer (LNCaP, 22Rv1, PC3, and DU145) and normal (PWR1E and RWPE1) cell lines were cultured in air and hypoxia. The performance of 16 HKGs was assessed using Normfinder and coefficient of variation. In silico promoter analysis was performed to identify putative hypoxia response elements (HREs). The impact of the endogenous control on expression levels of HIF1A and GSTP1 was investigated by qRT‐PCR in cell lines and tissue specimens respectively. RESULTS Hypoxia altered expression of several HKGs: IPO8, B2M, and PGK1. The most stably expressed HKGs were ACTB, PPIA, and UBC. Both UBC and ACTB showed constitutive expression of HIF1A in air and hypoxia, while PGK1 falsely implied a sixfold hypoxia‐induced down‐regulation. In prostate tumors, UBC and PGK1 both revealed down‐regulation of GSTP1 relative to matched benign, whereas ACTB showed variability. CONCLUSIONS This study demonstrates that no universal endogenous control exists for gene expression studies, even within one disease type. It highlights the importance of validating expression of intended HKGs between different sample types and environmental exposures. Prostate 73: 382–390, 2013. © 2012 Wiley Periodicals, Inc.